THE ACQUISITION OF MANDAILING LANGUAGE AND LANGUAGE DISORDER AT THE SYNTACTIC LEVEL IN TWO YEARS OLD CHILD - Anni Marhamah; Muhammad Ikbal (Jurnal Sintaksis, 2020)
This article aimed to analyze the acquisition of Mandailing language and language disorder at the syntactic level in two years old child in the term of Psycholinguistics. This study focused on these four purposes; describe the types of nouns, verbs, and adjective obtained by 2 years old child, describe the dominant word-class obtained by the child, describe the word in what meaning field the dominant child gained and describe language disorders that occur in children. The source of this study was a two years old child. The child named Nazla Yusyifa. The language the child used was Mandailing language. The data was collected in the form of recording of the child's speech with her parents. The linguistic aspect analyzed in this study was the syntactic level. The analysis was conducted qualitatively and quantitatively. Analyzing data was done with four steps, namely: Data Transcription, Data Selection, Data Classification and Exposure of Data Analysis Results.